Land inventory of historical and cultural purpose - Novakovska, I.; Skrypnyk, L.; Novakovsky, D. (Land Management, Cadastre and Land Monitoring, 2022)
The purposes of conducting an inventory of land plots and aspects of the legal regime of land use of historical and cultural purposes are presented. Problematic issues concerning the initial stage of the inventory of these lands within the settlements of Chernivtsi region are considered. The normative-legal basis for the establishment of protection zones of historical and cultural objects and their classification are analyzed. The peculiarities of the functioning of the program of land use and protection of the city of Kyiv and the distribution of the territory of the capital of Ukraine by historical areas are considered. The peculiarities of the inventory of land plots according to the Regional Program of Urban Cadastre Development and Spatial Planning for 2021-2025, which include objects of historical and cultural significance in the Lviv region, are described. A comparison was made between the problematic issues in the absence of inventory of historical and cultural lands, in particular the inclusion of objects in the databases of the state land cadastre, and the advantages that occur if the relevant inventory procedure.Key words: land relations, inventory, objects of historical and cultural purpose, land legislation.